Impaired Baroreflex Function in an Ovine Model of Chronic Heart Failure Induced by Multiple Coronary Microembolizations - Abukar, Yonis; Lever, Nigel; Pachen, Mridula; LeGrice, Ian J.; Ramchandra, Rohit (Frontiers in Physiology, 2019)
Testing new therapies in heart failure (HF) requires a chronic stable model of HF in large animals. Microembolization of the coronary arteries has been used to model HF previously, however, neural control has not been previously explored in this model. Thus the aim of this study was to further characterize neural control in this model of HF. HF was induced by infusion of microspheres (45 micron; 1.3 mL) into the proximal left coronary artery or left descending coronary arteries, with three sequential embolizations over 3 weeks. Twelve to 14 weeks after the final embolization, and when ejection fraction had decreased below 45%, animals were instrumented to record blood pressure and heart rate. Baroreflex control of heart rate was investigated in conscious animals. Additionally, pressure-volume loops were constructed under anaesthesia. Embolization-induced HF was associated with a decrease in mean arterial pressure (67 ± 2 vs 85 ± 4 mmHg, P<0.05), an increase in heart rate (108 ± 4 vs 94 ± 4 bpm, P<0.05) and a significant increase in left ventricular end-diastolic pressure (11.4 ± 2 vs 6.2 ± 1 mmHg, P<0.01). Under conscious conditions, there was a significant decrease in the gain (-8.2 ± 2 vs -4.1 ± 1 beats/min/mmHg, P<0.05) as well as the lower plateau of the baroreflex in HF compared to control animals. HF was also associated with significantly increased respiratory rate (107 ± 4 vs 87 ± 4 breaths/min, P<0.01) and incidence of apneas (520 ± 24 vs 191 ± 8 apnea periods>4s, P<0.05), compared to control sheep. The microembolization model of heart failure is associated with an increase in left ventricular end-diastolic pressure, impaired cardiac function and altered baroreflex control of the heart. These findings suggest this chronic model of HF is appropriate to use for investigating interventions aimed at improving neural control in HF.